EFFECT OF LIGHT QUALITIES AND STORAGE PERIODS ON THE GERMINATION OF PENNISETUM POLYSTACHION SEEDS*) - TJITROSEMITO, S (BIOTROPIA, 2011)
Seeds of the yellowish inflorescence strain of Pennisetum polystachion, collected from the field in Indonesia, were kept in the dark for 30 days, then germinated in 12-h light and 24-h light under various light qualities, namely, white, black, blue, red and far-red. There was no effect of photo-period to seed germination. Percent of seed germination under white, red, far-red, blue and dark were 49, 43, 22, 11 and 2%, respectively. White and red light did not cause any difference to seed germination. Seeds kept in 12-h light alternating with 12-h dark and 24-h dark for 15 and 30 days were tested for germination. Results showed that light condition during seed storage did not effect seed germination. Long storage period resulted in more seed germination. During seed germination test, effect of light played a great role on increasing seed germination.